Optimalisasi Menghafal Al-Qur'an: Penerapan Metode Neuro Linguistic Programming (NLP) di Pesantren Islamic Centre Sumut - Nahar, Syamsu; Daulay, Nurul Sakinah; Nazri, M. (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research aims to analyze the application of NLP/Neuro Linguistic Programming methods in improving the quality of memorizing the Quran at the Islamic Center. Sumut is well organized from the formation of the tasmi class, creating a conversational atmosphere to memorize, reminding that everything is aimed at and meaningful, understanding the learning style of the pupils, stimulating the brain performance to the maximum, giving judgment, identifying the problems of central and central difficulties in memorizing, giving motivation and solutions in the form of positive advice to the central and central, and giving reinforcement or strengthening. The data collection techniques used are observations, interviews, and documentation studies. The results of the research show that the implementation of the NLP/Neuro Linguistic Programming method improves the quality of memorizing the Qur'an at the Islamic Centre. Sumut is well organized starting from the formation of the tasmi class, creates a conversation atmosphere to memorize, reminds that everything is aimed at and meaningful, understands the learning style of the pupils, stimulates the brain performance to the maximum, gives judgment, identifies the problems of the centri and santriwati difficulties in falsifying, gives motivation and solutions in the form of positive advice to the santri and santriwati, gives reinforcement or strengthening, and evaluates the application of the NLP method in the Madrasah Hifzil Islamic Quran Centre.